Bibliometric Analysis of Teacher Leadership Using VOSviewer - Hidayat, Rais; Patras, Yuyun Elizabeth; Sampaleng, Donna; Gunawan, Yusuf (JURNAL AL-TANZIM, 2023)
This article aims to identify publications on the teacher leadership theme comprehensively. The publication data is from articles, reviews, and English and comes from the Scopus database from 1993 to 2022. The keyword used in the data search is "teacher leadership." The investigation found 753 documents later used as the basis for conducting Bibliometric studies.   This Bibliometric analysis method uses Vosviewer software. All data is classified by trend; country; organization; source; author, relationship between authors; and teacher leadership research hotspots which were then analyzed using the Vosviewer software. The main findings of the study include: the trend of teacher leadership publication continues to increase, and the future direction of teacher leadership research will concern two domains, namely: new word/phrase domains connected to teacher leadership, such as COVID, leadership style, self-efficacy, diversity, school principal, evidence,  professional learning, community; and domain teacher leadership research processes or methods such as mix-method, instrument, questionnaire, and data processing. The findings of this study can be used as one of the materials for making decisions related to improving teacher leadership publications.